Missionários alemães no Estado do Maranhão e Grão-Pará - Jaeckel, Volker (Contingentia, 2008)
This paper discusses the role of German Jesuit priests in the conquest of the lower amazon area in the 17th century. The Luxemburg missionary John Philip Bettendorff, founder of the second largest city of Pará, Santarém, was one of the most important figures while colonizing the Estate of Maranhão e Great-Pará. His chronicle is not only an important testimony of the settlements’ history but also of the Jesuit activities as handicraft workers and artists while catechizing this region. Thus, it comprehends a part of the rich cultural memory of colonial Brazil.